Decompression of Facial Nerve after Temporal Bone Fracture: about 20 Cases - Kolsi, Naourez; Jellai, Sondes; Ferjaoui, Mahdi; Bouaziz, Nawress; Korbi, Amel; Harrathi, Khaled; Bouattay, Rachida; Koubaa, Jamel (Journal of Otorhinolaryngology and Facial Plastic Surgery, 2021)
Background: Seven to ten percent of facial nerve paralysis occurs in patients with temporal bone fracture. It has become increasingly common due to the development of human activity. One of the main topics of discussion is facial nerve injury management resulting from temporal bone trauma. The purpose of this study is to report the paralysis of facial nerve after temporal bone fractures. Aim: In this study, our goal was to record the facial profile of rhinoplasty applicants in Shiraz. Methods: This retrospective study analyzed 20 cases of traumatic paralysis of facial nerve, which underwent facial nerve decompression. Results: Recovery rate was correlated to the delay of surgery. 83.3% of patients who underwent decompression surgery within the first 2 weeks after trauma had an excellent therapeutic outcome (HB grading I-II) and the difference was statistically significant (p=0.000). Conclusion: Facial nerve paralysis surgical management after bone fracture is controversial. The decision must be taken according to the type of paralysis and the radiological electrophysiological and evolutionary data.